2016
DOI: 10.1038/nmicrobiol.2016.174
|View full text |Cite
|
Sign up to set email alerts
|

A quorum-sensing signal promotes host tolerance training through HDAC1-mediated epigenetic reprogramming

Abstract: The mechanisms by which pathogens evade elimination without affecting host fitness are not well understood. For the pathogen Pseudomonas aeruginosa, this evasion appears to be triggered by excretion of the quorum sensing (QS) molecule 2-aminoacetophenone (2-AA), which dampens host immune responses and modulates host metabolism, thereby enabling the bacteria to persist at a high burden level. Here, we examined how 2-AA trains host tissues to become tolerant to a high bacterial burden, without compromising host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 55 publications
5
76
0
Order By: Relevance
“…Recently, we have demonstrated that the bacterial excreted QS small molecule 2-AA trains the host to tolerate a sustained presence of P. aeruginosa by a HDAC1-mediated epigenetic reprogramming (Bandyopadhaya et al, 2016b). In this study, we undertook further molecular analyses of alterations in intracellular signaling components and epigenetic regulators following 2-AA-mediated tolerization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have demonstrated that the bacterial excreted QS small molecule 2-AA trains the host to tolerate a sustained presence of P. aeruginosa by a HDAC1-mediated epigenetic reprogramming (Bandyopadhaya et al, 2016b). In this study, we undertook further molecular analyses of alterations in intracellular signaling components and epigenetic regulators following 2-AA-mediated tolerization.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated the role of multiple virulence factor regulator (MvfR), also known as PqsR, in the formation of AT/P cells ( 14 16 ) and the regulation of various virulence functions in P. aeruginosa ( 14 17 , 19 25 ). MvfR is a quorum sensing transcriptional regulator that regulates virulence functions critical for acute, persistent, and relapsing infections, making it a high-interest novel drug target for treatment of P. aeruginosa infections ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Pseudomonas aeruginosa infection, the bacteria‐induced infection tolerance seems to be regulated via HDAC1. Therefore, it was verified a hypo‐acetylation of lysine 1 of histone H3 at pro‐inflammatory cytokine promoter .…”
Section: Discussionmentioning
confidence: 88%